Ethno-cultural basis of the process of formation of the Crimean Tatar artistic culture and decorative art (part 4)* - Ismet Zaatov (Крымское историческое обозрение)
n the article an attempt is made to trace the stages of development of the process of the Kypchak-Tatar – Turko-Seljuk Turkization and the beginning of the process of Asia Minor–Central Asian Islamization of the population of the peninsula and formation of artistic culture and decorative art of the Crimean Tatars during the formation of the foundations of the Crimean Tatar statehood in the Black Sea uluses of the Golden Horde.